Insights into Solea senegalensis Reproduction Through Gonadal Tissue Methylation Analysis and Transcriptomic Integration - Daniel Ramírez; Marco Anaya-Romero; María Esther Rodríguez; Alberto Arias-Pérez; Robert Mukiibi; Helena D’Cotta; Diego Robledo; Laureana Rebordinos (Biomolecules)
Fish exhibit diverse mechanisms of sex differentiation and determination, shaped by both external and internal influences, often regulated by distinct DNA methylation patterns responding to environmental changes. In S. senegalensis aquaculture, reproductive issues in captivity pose significant challenges, particularly the lack of fertilization capabilities in captive-bred males, hindering genetic improvement measures. This study analyzed the methylation patterns and transcriptomic profiles in gonadal tissue DNA from groups differing in rearing conditions and sexual maturity stages. RRBS (Reduced Representation Bisulfite Sequencing) was employed to detect notable methylation variations across groups, while RNA was extracted and sequenced for differential expression analysis. Our findings suggest that DNA methylation significantly regulates gene expression, acting as a mechanism that can both repress and enhance gene expression depending on the genomic context. The complexity of this epigenetic mechanism is evident from the varying levels of methylation and correlation rates observed in different CpGs neighboring specific genes linked to reproduction. Differential methylation comparisons revealed the highest number of differently methylated CpGs between maturation stages, followed by rearing conditions, and lastly between sexes. These findings underscore the crucial role of methylation in regulating gene expression and its potential role in sex differentiation, highlighting the complex interplay between epigenetic modifications and gene expression.